Research Trends on the Integration of Science and Character Education: A Bibliometric Analysis Review - Hamdi, H; Riduan, Ahmad; Anggraini , Puspita Ais; Baehaqi , Luqman; Syahid , Abdul; Huda , Ali Anhar Syi’bul; Mualimin , M (Universitas Muhammadiyah Surakarta, 2025)
Research on multicultural leadership has not systematically referred to the principles of the Qur'an in the context of Islamic education. This research aims to examine the principles of leadership in multicultural Islamic education based on the perspective of the Qur'an, focusing on universal values that support harmonization in a pluralistic educational environment. The research method used is qualitative with a library research approach, where data is collected through an in-depth study of Qur'anic verses, classical and contemporary interpretations, and literature related to multicultural leadership and education. The results of this study show that the Qur'an establishes five main principles of leadership in multicultural Islamic education: Amanah, al-'is (justice), ash-shura (deliberation), at-tasamuh (tolerance), and al-hikmah (wisdom). These principles are theoretical and can be implemented in practice through inclusive policies, the development of multicultural-based curricula, and the fostering of respect for differences among learners. This study concludes that integrating Qur'anic values in Islamic education leadership can be an effective solution to create an environment that is harmonious, equitable, and responsive to diversity. Practical recommendations include multicultural leadership training for educators and strengthening collaboration between educational institutions to promote unity in diversity. These findings contribute to a theoretical model of Islamic educational leadership based on Qur'anic values integrated with modern multiculturalism.